Decision Making: Thermal Ablation Options for Small Renal Masses - McCarthy, Colin J.; Gervais, Debra A. (Seminars in Interventional Radiology, 2017)
Renal cell carcinoma is a relatively common tumor, with an estimated 63,000 new cases being diagnosed in the United States in 2016. Surgery, be it with partial or total nephrectomy, is considered the mainstay of treatment for many patients. However, those patients with small renal masses, typically less than 3 to 4 cm in size who are deemed unsuitable for surgery, may be suitable for percutaneous thermal ablation. We review the various treatment modalities, including radiofrequency ablation, microwave ablation, and cryoablation; discuss the advantages and disadvantages of each method; and review the latest data concerning the performance of the various ablative modalities compared with each other, and compared with surgery.
Keywords: renal cell carcinoma; microwave ablation; cryoablation; radiofrequency ablation; interventional radiology